A single door to the Kulliyyah of Information and Communication Technology (KICT) online services - Ayu, Media Anugerah; Mohamed, Elgharabawy; Mohammad, Al-Mohaifer; Rameez, Mamdooh (IIUM Press, 2011)

(untitled)
Web based systems are used excessively in most organizations nowadays. To access restricted areas on service provider's servers, users have to provide credentials to login and authenticate themselves. Nowadays, users have to keep track of many credentials for each almost each web service they wish to use. This chapter focuses on open source web services provided by Kulliyyah of Information and Communication Technology (KICT) in International Islamic University Malaysia. The chapter tries to study the available web services and tries to propose a solution for a single-sign-on for web services in KICT, HUM